Quantification of mast cells in central centrifugal cicatricial alopeciaCapsule Summary - Sydney Look-Why, BA; Jared Goldberg, BS; Claire Alexanian, MD; Nicole Rogers, MD; Nikita N.M. Coleman, BA, BS; Yolanda M. Lenzy, MD; Eric Pinos, BS; Lynne J. Goldberg, MD (Elsevier, 2024)
Background: Mast cells (MCs) have recently been implicated in lymphocytic scarring alopecias, which may share a common pathogenesis. MCs in central centrifugal cicatricial alopecia (CCCA) have not been studied. Objective: We looked for the presence of MCs in CCCA using 2 different stains to see if their numbers correlated with the number of hair follicles, the degree of inflammation and perifollicular fibrosis, disease duration and severity, and patient symptoms. Methods: We performed a retrospective review of biopsies of patients diagnosed with CCCA, tabulated MC counts and correlated them with histopathologic and clinical findings. Results: MC counts were significantly greater using immunoperoxidase staining with CD117 than Giemsa stain, and more were present when the isthmus level was included with the infundibulum. MC counts with CD117 immunostain significantly correlated with the degree of inflammation. MC counts with both stains were significantly associated with the degree of fibrosis independently and after controlling for other factors. Limitations: The study was limited by insufficient tissue remaining in a small number of the transversely cut blocks. Conclusion: Our findings may have therapeutic implications for CCCA and other types of lymphocytic scarring alopecia.